The efficacy of nutritional screening tools for diagnosis of malnutrition in children with epidermolysis bullosa - Victoria Ojukwu; Olesia Singh (Bogomolets National Medical University, 2022)
malnutrition worsens the course of the main disease and requires early diagnosis. We were aiming to identify the prevalence of malnutrition and to elicit the most effective nutritional screening tool for malnutrition in children with epidermolysis bullosa. A cross-sectional study for prevalence and suitable nutritional screening tool for malnutrition of 26 patients of age 2 to 18 years with mean age 8,65±3,86 were carried out. There were 14 females (53.8%) and 12 males (46.2%). Anthropometric data, medical and nutrition history were obtained. The following nutritional screening tools were studied: PYMS, STAMP, STRONGkids, and we calculated the degree of malnutrition with online calculator PediTools, taking into account Z-score of anthropometric indicators. We evaluated the validity of these screening tools by calculating the sensitivity and specificity alongside their accuracy with the 2x2 table using MEDCALC statistical software. According to clinical manifestation, there were 11 (42.3%) children with severe malnutrition, 7 (26.9%) with moderate and 8 (30.8%) without malnutrition. Using different nutritional screening tools we found the following: on STRONGkids, 14 (53.9%) had low risk, 3 (11.5%) - moderate risk, 9 (34.6%) - high risk of malnutrition, sensitivity was 66.67%, specificity - 100%, accuracy - 76.92%. On STAMP we found, with 5 (19.2%) low risk, 7 (26.9%) - moderate risk, 14 (53.9%) - severe risk, sensitivity was 100%, specificity - 62.5%, accuracy - 88.46%. On PYMS, there were 11 (42.3%) with low risk and 8 (30.8%) with moderate risk, 7 (26.9%) with severe risk; sensitivity was 83.33%, specificity - 100 %, accuracy - 88.46%. We did not find a good nutritional tool for screening of malnutrition in patients with epidermolysis bullosa. But PYMS have shown more efficiency in comparison with STRONGkids and STAMP because it includes evaluation of BMI which makes it possible to evaluate whether the body mass is insufficient or normal.